Is revascularization of immature permanent teeth an effective and reproducible technique?. Issue 6 (15th September 2015) - Chen, Yu‐Po; Jovani‐Sancho, Maria del Mar; Sheth, Chirag C.
Abstract: Background: Revascularization has been proposed as an improved alternative treatment for irreversibly damaged pulp of immature teeth as it has been shown to preserve the potential for continued root growth in treated teeth. Aim: To review clinical cases of revascularization in humans to evaluate their utility and reproducibility. Material and methods: A structured electronic search of scientific articles published between 2001 and 2014 was carried out using the following keywords: 'pulp revascularization', 'pulp revitalization' and/or 'immature tooth'. Clinical revascularization cases conducted on human subjects were selected, reviewed and organized into two charts including patient information, diagnostic information, treatment and results in follow‐up visits. Results: Ninety‐seven of 101 teeth (96.0%) were successfully treated with the revascularization technique. The range of technique variations available for irrigation, disinfection and blood clot induction have a negligible impact on the clinical outcome variables tested in our analysis. During the follow‐up visits, apical closure was detected in fewer cases (55.4%) as compared to the other apexogenesis phenomena (increased root length, 76.2%; increased root width, 79.2%). Conclusions: The review shows that the revascularization technique showed marked increase in the root length, width and apical closure in the cases that were reported independently of clinical variables such as operator and material selection and individual differences in protocols.